Stabilized solid garnet electrolyte and methods thereof

By acidic treatment and proton exchange on the surface of garnet electrolyte materials, the problem of the material forming a carbonate surface layer in the air is solved, and the air stability and performance of the material are improved.

JP2025038209APending Publication Date: 2025-03-18CORNING INC

Patent Information

Application Number
JP2024226125
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2014-11-26
Filing Date
2024-12-23
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing garnet electrolyte materials easily form electrically insulated carbonate surfaces when they come into contact with air, affecting the performance and stability of the battery.

Method used

By acidic treatment of the surface of the garnet electrolyte material, the carbonate surface is removed and the superprotonated surface is formed through proton exchange, improving the air stability and carbon dioxide stability of the material.

Benefits of technology

It achieves the stability and performance of garnet electrolyte materials in the air, reduces the resistance and polarization of the battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038209000006
    Figure 2025038209000006
  • Figure 2025038209000007
    Figure 2025038209000007
  • Figure 2025038209000008
    Figure 2025038209000008
Patent Text Reader

Abstract

To provide a stabilized solid garnet electrolyte article, a method of making the stabilized solid garnet electrolyte article, and a method for using the stabilized solid garnet electrolyte article in an energy storage device.SOLUTION: A solid garnet composition comprises: a bulk composition consisting of or consisting essentially of a lithium garnet; and a surface composition consisting of or consisting essentially of a surface protonated garnet on at least a portion of the exterior surface of the lithium garnet, wherein the surface composition is compositionally stable in air and insensitive to carbon dioxide.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Priority

[0001] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Patent Application No. 62 / 084,907, filed November 26, 2014, the contents of which are relied upon and incorporated by reference in their entirety into this application.

[0002] The entire disclosure of any publication or patent document mentioned herein is incorporated by reference. [Technical field]

[0003] The present disclosure relates to stabilized solid garnet electrolyte articles, as well as methods of making and using the stabilized solid garnet electrolyte articles in energy storage devices. Summary of the Invention

[0004] In embodiments, the present disclosure provides stabilized solid garnet electrolyte articles, as well as methods of making and using the stabilized solid garnet electrolyte articles in energy storage devices. [Brief description of the drawings]

[0005] [Figure 1] Schematic of applicable acid treatment and regeneration steps [Diagram 2] FIG. 2 is a schematic cross-sectional view of a test cell assembly (200) incorporating a lithium metal anode (150) in contact with a solid garnet electrolyte (110) of the present disclosure. [Diagram 3] Comparison of operating cell voltage for acid-treated garnet pellets (diamonds, 310) and untreated garnet pellets (squares, 300) (control) as a function of current density [Figure 4] Example long-term operating cell voltages for acid-treated garnet pellets at high current density of 1.0 mA / cm [Diagram 5]TGA traces comparing an untreated garnet control (500) sample with an acid-treated garnet (510) sample after exposure to ambient moisture. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] Various embodiments of the present disclosure will now be described in detail with reference to the drawings, where available. Reference to various embodiments is not intended to limit the scope of the invention, which is limited only by the claims appended hereto. Moreover, any examples described herein are not intended to be limiting, but merely to illustrate some of the many possible embodiments of the claimed invention.

[0007] definition "Air", "ambient air", "ambient atmosphere", "atmospheric air" or similar terms refer to the chemical constituents occurring in the Earth's atmosphere, e.g., dry air contains 78.09% nitrogen, 20.95% oxygen, 0.93% argon, 0.039% carbon dioxide, and small amounts of other gases. Moist air also contains water vapor.

[0008] "Compositionally stable" or like terms refer to a solid garnet composition of the present disclosure which, once formed, does not substantially change in composition, even when exposed to the ambient atmosphere for several hours or more.

[0009] "Air stable" or similar terms also refer to solid garnet compositions of the present disclosure which, once formed, do not substantially change in composition, e.g., when exposed to air or the ambient atmosphere for several hours or more.

[0010] "Insensitive to carbon dioxide" or similar terms also refer to solid garnet compositions of the present disclosure which, once formed, do not substantially change in composition even when exposed to, for example, air or an ambient atmosphere containing carbon dioxide for several hours or more.

[0011] The term "include," "includes," or similar terms means including but not limited to, i.e., inclusive and not exclusive.

[0012] For example, "about" used in describing embodiments of the present disclosure to modify amounts, concentrations, volumes, process temperatures, process times, yields, flow rates, pressures, viscosities, and similar values ​​and ranges of components in a composition, or dimensions of components, and similar values ​​and ranges, refers to variations in numerical quantities that may occur, for example: due to typical measuring and operating procedures used to prepare materials, compositions, complexes, concentrates, components, products, or formulations used; due to inadvertent errors in these procedures; due to differences in manufacture, source, or purity of starting materials or components used to carry out the method; and due to similar considerations. The term "about" also encompasses amounts that vary with aging of a composition or formulation having a particular initial concentration or mixture, and amounts that vary with mixing or processing of a composition or formulation having a particular initial concentration or mixture.

[0013] "Optional" or "optionally" means that the subsequently described event or circumstance may or may not occur, and includes cases where the event or circumstance occurs and cases where the event or circumstance does not occur.

[0014] As used herein, the indefinite article "a" or "an" and its corresponding definite articles "the," "the," "the" mean at least one or more than one, unless otherwise specified.

[0015] Abbreviations well known to those of skill in the art may be used (e.g., "h" or "hrs" for hours, "g" or "gm" for grams, "mL" for milliliters, and "rt" for room temperature, "nm" for nanometers, and similar abbreviations).

[0016] Specific and preferred values ​​disclosed for components, ingredients, additives, dimensions, conditions, times, and similar aspects and ranges thereof are for illustrative purposes only, and they do not exclude other explicit values ​​or other values ​​within explicit ranges. The compositions and methods of the present disclosure can include any value or any combination of the values, specific values, more specific values, and preferred values ​​set forth herein, including any intermediate values ​​and ranges expressly or implied.

[0017] 10 ‐4 With ceramic lithium electrolytes now known that have demonstrated practical conductivities in excess of S / cm (see Knauth, Solid State Ionics (2009) 180, 911-916), interest has focused on other ceramic Li-ion electrolytes that enable high energy cell construction. New designs rely on ceramic electrolytes to separate incompatible anode and cathode chemistries with hermetic isolation. For example, a new approach to lithium-sulfur cell chemistry combines an aqueous sulfur cathode with a lithium metal anode (see Visco, et al., U.S. Pat. No. 8,828,574).

[0018] To enable a Li-metal anode, the ceramic electrolyte must be stable to lithium metal contact. Currently, Li7La3Zr2O 12 Garnet phase electrolytes such as (LLZO) have high lithium-ion conductivity (10 ‐4They have demonstrated both high thermal conductivity (>3000 S / cm) and stability towards Li-metal contacts (Weppner, et. al., U.S. Pat. No. 8,658,317). Unfortunately, garnet materials are prone to the formation of an insulating film of lithium carbonate when exposed to ambient conditions (see Cheng, et. al., Phys. Chem. Chem. Phys., (2014) 16, 18294-18300). This insulating film can have a strong effect on the impedance of the cell if it is not removed. Cheng, et. al. suggest polishing under an inert atmosphere as a solution to remove the Li2CO3 insulating film. However, after polishing, the garnet material must be protected from further ambient exposure or the lithium carbonate insulating film will form again. To enable processing in ambient environments, it is desirable to be able to make the garnet electrolyte structure insensitive to carbon dioxide in the ambient environment.

[0019] Garnet materials can be reversibly converted to H in aqueous solution. + / Li + It is known that garnet materials can undergo reversible Li+ / H+ exchange (see Ma, C., et al., (2014), Excellent Stability of a Lithium-Ion-Conducting Solid Electrolyte upon Reversible Li+ / H+ Exchange in Aqueous Solutions. Angew. Chem. DOI: 10.1002 / ange.201408124). When the as-synthesized garnet material is immersed in neutral water, the pH of the aqueous phase changes according to the following formula:

[0020] [ka]

[0021] LiOH according to, for example, Li7La3Zr2O 12 (LLZO) garnet formation leads to a shift to basic pH.

[0022] The same reaction occurs at the surface of garnet materials operated in ambient air. LiOH is known to sorb or absorb atmospheric CO2 to form Li2CO3 (see Jaunsen, JR (1989) "The Behavior and Capabilities of Lithium Hydroxide Carbon Dioxide Scrubbers in a Deep Sea Environment," US Naval Academy Technical Report, USNA‐TSPR‐157.).

[0023] [ka]

[0024] or

[0025] [ka]

[0026] The end product of this reaction sequence is an insulating surface film of lithium carbonate (Li2CO3). A similar reaction sequence has been observed for LiLaTiO3 electrolytes (see Boulant, et. al., Dalton Trans. (2010) 39 3968-3975).

[0027] H + / Li + Since the exchange is reversible, the garnet material can be treated in acid to neutralize the surface of the garnet material and decompose the Li2CO3 formed. For example, Li2CO3 can be decomposed using HCl:

[0028] [ka]

[0029] In embodiments, the disclosed methods can effectively clean garnet surfaces, such as LiOH, Li2CO3, and similar species. The disclosed methods can also effectively regenerate lithium ion active garnet surfaces, such as those used in energy storage articles.

[0030] In embodiments, the present disclosure provides stabilized solid garnet electrolyte articles, as well as methods of making and using the stabilized solid garnet electrolyte articles in energy storage devices.

[0031] In embodiments, the present disclosure provides air-stabilized solid garnet compositions and solid electrolyte articles thereof, and the present disclosure provides methods of making and using said compositions and said stabilized solid garnet electrolyte articles.

[0032] In embodiments, the present disclosure provides a method for passivating a solid lithium garnet electrolyte against surface contamination by the surrounding atmosphere.

[0033] In embodiments, the present disclosure provides methods for treating a solid lithium garnet electrolyte, said treatment methods allowing for manipulation or processing of said garnet electrolyte in an ambient environment.

[0034] In embodiments, the present disclosure provides methods for regenerating passivated solid garnet electrolytes, in situ or ex situ, to generate active lithium ion surface species suitable for use in energy storage devices. The present disclosure provides examples of in situ regeneration.

[0035] In embodiments, the present disclosure provides a solution processing method for solid garnet electrolytes to clean Li2CO3 from the surface, which can result in improved cell performance.

[0036] In an embodiment, the present disclosure provides a passivation method, in which a garnet film having a lithium-containing surface is converted to a garnet film product having a lithium-deficient surface, the product being stable to, for example, atmospheric moisture, oxygen, and carbon dioxide. In an embodiment, the passivation method includes ion-exchange of lithium ions of the garnet film with protons (i.e., Li + / H + The resulting superprotonated membrane can be operated under ambient conditions without concern for the formation of a carbonate membrane. The superprotonated garnet can then be electrochemically converted back to the lithium-rich garnet using a lithium-containing electrode.

[0037] The present disclosure is advantageous in several aspects, including, for example: The treatment methods of the present disclosure remove resistive carbonate surface layers on garnet substrates and improve the performance of cells containing garnet electrolytes.

[0038] The preparation method involving contacting a garnet electrolyte with a protonic acid can be applied to many forms of garnet electrolyte where alternative surface treatment methods such as surface polishing are impractical. Exemplary garnet electrolyte forms that can be treated according to the methods of the present disclosure include: porous garnet surfaces (which may be useful for improving electrode contact); thin garnet coatings (e.g., less than 20 micrometers thick); thin garnet films (e.g., less than 200 micrometers thick, such as 150 micrometers, 100 micrometers, 50 micrometers, etc., including intermediate values ​​and ranges), and similar forms. For example, preparation methods involving acid treatment of lithium garnet electrolytes can be accomplished by brief exposure to acid, for example, 1-2 hours at ambient temperature.

[0039] Because the lithium ion species at the surface of the garnet electrolyte are chemically neutralized by the disclosed method, the formation of lithium carbonate is at least temporarily mitigated, allowing operation of the garnet film in ambient air, thereby simplifying the cell's construction and reducing fabrication costs.

[0040] In an embodiment, the method of the present disclosure provides a solid garnet composition, said solid garnet composition comprising: A bulk composition comprising lithium garnet; and a surface composition comprising a surface protonated garnet on at least a portion of an outer surface of the lithium garnet, the surface protonated portion of the garnet composition being compositionally stable in air and insensitive to carbon dioxide. Includes.

[0041] In an embodiment, the present disclosure provides a solid garnet composition, said solid garnet composition comprising: a bulk composition consisting of, or consisting essentially of, lithium garnet; and a surface composition consisting of, or consisting essentially of, a surface protonated garnet on at least a portion of an outer surface of said lithium garnet, said surface protonated garnet composition being compositionally stable in air and insensitive to carbon dioxide. Includes.

[0042] In an embodiment, the bulk lithium garnet may be, for example, of the formula Li7La3Zr2O 12 (LLZO), the surface protonated garnet may have the formula Li (7‐x) H x La3Zr2O 12 (where x is 0.1 to 7).

[0043] In an embodiment, the bulk lithium garnet may be, for example, of the formula Li 6.75 La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 The surface protonated garnet may have, for example, Li (6.75‐x) H x La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 (where x is 0.1 to 6.75).

[0044] In embodiments, the surface protonated garnet can be formed on opposing sides or faces of the acid-treated solid garnet composition, for example on the major or minor faces of a treated film. The non-acid-treated surfaces can be protected, for example with a mask layer. In embodiments, the surface protonated garnet can be formed, for example, on the entire outer surface of the lithium garnet.

[0045] In an embodiment, the solid garnet composition of the present disclosure may be, for example, of the formula Li (6.75‐x) H x La 2.9 Ga 0.1 Zr 1.75 Nb 0.25 O 12 or a surface composition of formula Li (7‐z‐x) H x La 3‐y Ga y Zr 2‐z Nb z O 12 or a combination thereof (wherein x is 0.1 to 7, y is 0.1 to 0.3, and z is 0.1 to 0.3), for example a compound having the general formula Li 7‐z La 3‐y Ga y Zr 2‐z Nb z O 12 of, or more specifically, the formula Li 6.75 La 2.9 Ga 0.1 Zr 1.75 Nb 0.25 O 12 The doped LLZO can be used.

[0046] Garnet pellets are one example of a suitable garnet. The compositions and methods of making and using of the present disclosure are suitable for all garnet films, regardless of the method of making the bulk garnet, as long as the bulk garnet is exposed to an ambient atmosphere that contains, for example, the presence of water, carbon dioxide, or the like, since the garnet will form an aprotic passivation layer if not processed according to the present disclosure.

[0047] In an embodiment, the protonated garnet on at least a portion of the outer surface of the lithium garnet includes, for example, the entire outer surface of the lithium garnet.

[0048] In an embodiment, the protonated garnet on at least a portion of said outer surface of said lithium garnet comprises a layer having a thickness of, for example, 0.1 to 100 nm.

[0049] In an embodiment, the surface composition has a lithium concentration of 0.1 to 46 mol %.

[0050] In an embodiment, the surface composition can be substantially free of electrically insulating Li surface species, for example, less than 0-10 mol %.

[0051] In an embodiment, the surface composition comprises a surface that does not include at least one of LiOH, Li2CO3, or a combination thereof.

[0052] In an embodiment, the present disclosure provides: 1. A protective anode structure comprising: A first layer comprising a solid ceramic garnet electrolyte composition comprising a solid garnet composition: A bulk composition comprising lithium garnet; and A surface composition comprising a protonated garnet on at least a portion of an outer surface of the lithium garnet. a first layer comprising: a second layer comprising a source of lithium metal wherein the first layer and the second layer are in physical contact and are encapsulated within the protective anode structure; and Cathode The present invention provides a composite electrolyte structure comprising:

[0053] In embodiments, the composite electrolyte structure may further comprise an aqueous catholyte, for example between the protective anode structure and the cathode, and in contact with the protective anode structure and the cathode.

[0054] In embodiments, the cathode may be, for example, a lithium cobalt oxide compound of formula LiCoO2.

[0055] In an embodiment, the present disclosure provides a method of making the solid garnet composition described above, the method comprising: contacting an air-sensitive lithium-containing solid garnet electrolyte with a protonic acid to form a solid garnet composition having a protonated surface; Includes.

[0056] In embodiments, the protonated surface solid garnet composition is compositionally stable in air and insensitive to carbon dioxide.

[0057] In embodiments, the protic acid may be selected from at least one of: an inorganic acid, such as, for example, HCl, H3PO4, HNO3, H2SO4, and similar acids or mixtures thereof; an organic acid, such as, for example, acetic acid or similar organic acids or mixtures thereof; or a combination of inorganic and organic acids.

[0058] In embodiments, the method of making can further include, for example, contacting the air-stable, carbon dioxide insensitive solid garnet electrolyte having the protonated surface with a source of lithium ions to regenerate an air-sensitive lithium-containing solid garnet electrolyte.

[0059] In embodiments, the contact with the source of lithium ions can be achieved, for example, within a sealed cell structure, e.g., by treating the garnet electrolyte with a source of lithium ions, where the garnet electrolyte is within the sealed cell structure and not on a bare membrane.

[0060] In embodiments, the source of lithium ions may be, for example, lithium metal.

[0061] In an embodiment, the present disclosure provides: Ion-exchanging the lithium ions on the air-sensitive lithium-containing solid garnet film with protons to form an air-stable, carbon dioxide-insensitive solid garnet electrolyte having a lithium-deficient protonated surface. The present invention provides a method for passivation comprising the steps of:

[0062] Referring to the drawings, Figure 1 is a schematic diagram (100) illustrating several aspects of the disclosed method. In embodiments, when a film (110), such as LLZO, is exposed (115) to an ambient atmosphere or air containing, for example, carbon dioxide and water, a surface layer containing LiOH and Li2CO3 (120) and trace amounts of HLZO (130) can form on the exposed surface, i.e., a product of exposure of LLZO to the ambient atmosphere.

[0063] In embodiments, the air-exposed surface can be repaired by treating the affected surface with a suitable protonic acid source (135) to form a membrane (140) having a protonated surface composition (e.g., on one or more sides of the membrane, on two opposing sides of the membrane, or completely surrounding or encapsulating the LLZO (110) as shown), or a membrane (140) composed of, for example, an HLZO layer, which is distinguishable from the original traces of HLZO in that the amount of proton exchange is significantly higher than the level of HLZO formed by ambient exposure. The HLZO layer formed by acid exposure can be referred to as "super-protonated". This super-protonated surface is relatively resistant to further reaction with ambient moisture, making the surface stable against the formation of a surface contamination layer (120) for periods exceeding several hours, allowing for substantial operating times under ambient conditions.

[0064] In an embodiment, a clean membrane (110) can be treated (135) with a suitable protonic acid source to directly form a membrane (140) having a protonated surface composition (136) without the appearance of LiOH and Li2CO3 (120) surface contaminants and HLZO (130).

[0065] In an embodiment, at least a portion of the surface of a clean membrane (110), such as an LLZO or similar membrane, can be contacted or directly treated (135) with a protonic acid source to form a membrane product (140) having a bulk or interior composition (110), such as LLZO, and a protonated surface composition (136), such as HLZO, in one or more protonic acid source contact regions. The products (140), and similarly contacted membranes, are stabilized solid garnet electrolyte materials that can be further processed or manipulated in an ambient atmosphere to create or fabricate (145) articles or devices (e.g., cell assemblies) comprising the surface protonated garnet electrolyte product (140).

[0066] In an embodiment, the assembled cell (160) may include, for example, the surface-protonated garnet electrolyte product (140) described above, a lithium metal source (150), and a glass tube or cylinder or similar container or separator (104), which combination allows for lithium ion flux (155) from the lithium metal source (150) to and through the adjacent protonated surface composition (136).

[0067] In embodiments, assembled cells (160) can be tested (165) to measure the lithium ion flux and lifetime characteristics of the protonated surface composition (136). In this cell testing, the protonated surface composition (136), e.g., one or more HLZO surface layer compositions, can be determined, for example, by the following reaction:

[0068] [ka]

[0069] According to the Li metal + The flux (170) significantly converts or regenerates the LLZO bulk composition in contact with the lithium ion source (150) back to the original lithiated surface composition (110) or close to it, or other similar original composition.

[0070] This reaction can be carried out by reacting one or more of the protonated surface layer compositions with, for example, Li + High Li exceeding 1M + This does not occur in practical devices without contact with a solution having a concentration of 0.1% Cr, but such contact, if achieved in an ambient environment, regenerates the unstable LLZO or similar garnet composition. EXAMPLES

[0071] The following example or examples demonstrate the preparation, use, and analysis of the articles of the present disclosure in accordance with the above general procedures.

[0072] Example 1. Preparation of sintered garnet films The general stoichiometric formula is: Li 7‐z La 3‐y Ga y Zr 2‐z Nb z O 12 A gallium and niobium dual-doped composition having the formula (where z is 0.1-0.3 and y is 0.1-0.3) was synthesized as follows.

[0073] Suitable starting garnet powders were prepared from oxide precursors such as Li2CO3, LiOH, La2O3, ZrO2, Ga2O3, Nb2O5, Al2O3, AlOOH, and similar components. The powders were thoroughly dry mixed with ZrO2 media using turbulent mixing for example for 30-60 minutes and wet mixed in a liquid carrier such as isopropanol (IPA) or deionized water. The starting components were first mixed using a vibratory mixer for 1-2 hours until the mixed components were deagglomerated. The batch was then ball milled for about 1-2 hours for further mixing. The preferred total mixing time was, for example, less than 6 hours to avoid significant interaction between the liquid carrier and the precursor components. The resulting slurry was then dried at 100°C for 1-2 days. The dried powder was then ready for calcination. Calcination temperature is composition dependent. The low temperature composition can be dried, for example, at 1000° C. to 1100° C., while the high temperature composition can be dried up to 1200° C. The dried powder was calcined at 1100° C. for 6 hours to form a garnet structure having more than 90% cubic lithium garnet phase. The powder was then placed in a platinum crucible with a refractory sheet cover such as pure alumina.

[0074] The garnet powder was then pressed without any additives to form dry thick pellets. The thick pellets were protected with platinum to minimize air contact and sintered in air. The gallium and niobium dual doped lithium garnet has a low sintering temperature of 1000°C to 1200°C depending on the doping level, e.g., 0.1 to 0.5 for gallium and niobium, respectively, in the stoichiometric range. Thin slices (or films) of 27 mm diameter and 0.5 mm thickness were cut from the pellets. The cut films are the specimens used in cell testing (see Example 3 below). Examples of these compositions include Li 6.75 La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 which is an example of low level gallium doping, such as 0.1 to 0.5 gallium in the stoichiometric range.

[0075] After calcination, the powders were ground by dry ball or dry jet mill. Ball milling was a very fast and low cost grinding process. After ball milling, the powders typically had a bimodal distribution, such as 0.5-0.8 micrometers and 6-8 micrometers, with no agglomerates present. Jet milling is a high energy process, and very fine powders can be obtained by particle collision or by using an impact liner surface (ZrO2, alumina, tungsten, etc.). Lithium garnet requires a ZrO2 liner. After jet milling, the powders typically have a unimodal distribution with a D50 of approximately 0.5-0.8 micrometers. However, jet milled powders tend to form some agglomerates, and storage may require sealed conditions.

[0076] Garnet cylindrical solids can be made by dry pressing. The powder is preferably free of agglomerates, so deagglomeration may be necessary. The powder is first evenly placed in a die and then tapped. The tapping action was necessary because it ensures that the powder compresses naturally. A vacuum die is then used to remove any large voids. To ensure complete compression, the tapping action usually takes 1-5 minutes, followed by pressing at a force of over 13,000 pounds (5896.7008 kg), or 7000 psi (48263320 Pa), for 2-4 minutes.

[0077] Optimal sintering conditions may depend on the composition. For the disclosed compositions, sintering conditions may be, for example, 1100°C-1180°C for 2-15 hours. This higher temperature and longer hold time can significantly increase the degree of sintering, but is less economical and may cause grain growth. Preferred sintering conditions were higher temperatures with shorter hold times, or lower temperatures with extended hold times. Typical sintering conditions were 1120°C for 6 hours for one composition and 1180°C for 10 hours for another composition. After sintering, the geometric density was measured to ensure that the density was greater than 4.5 g / cc.

[0078] The cylindrical solids of lithium garnet were mechanically cut into thin disks using a precision diamond blade wet saw. It was observed that using mineral oil cutting medium and high cutting speeds improved disk quality. The finished disks were 0.4-0.8 mm thick with a thickness variation of 0.040 mm across the disk. Further dry grinding could be performed to obtain thinner disks. The thin films are then cut to 27 mm diameter by laser cutting for cell discharge testing and to provide ionic conductivity to the samples.

[0079] In this example, the lithium garnet composition has the formula Li 6.75 La 2.9 Ga 0.1 Zr 1.75 Nb 0.25 O 12 and was dual doped. The powder was milled by ball milling and could have a bimodal particle size distribution, with the smaller particle size being 0.6-0.7 micrometers and the larger particle size being 7-8 micrometers. The bimodal distribution was favorable for compaction of the particles during the tapping action.

[0080] The height of the cylindrical solids was quantified to be between 12 mm (60 g) and 22 mm (80 g) after sintering. The die diameter was 1.5 inches (or 38.1 mm) and samples were investigated at different sintering conditions to optimize the density and shrinkage under various conditions. The optimal sintering conditions were about 1170-1180°C for 6-15 hours. A number of films with a thickness of 0.5 mm were cut from these solids by diamond sawing. The quality of the slices may depend on the quality of the green body. Defects due to incomplete filling will be reflected as point or line defects during the sintering process. Thin films with flatness, toughness, hermeticity, and uniform thickness can be obtained using the above preparation method. The ionic conductivity of this composition is about 3-4×10 ‐4 S / cm.

[0081] Example 2 Garnet thin film Suitable starting garnet powders have been made from oxide precursors such as Li2CO3, LiOH, La2O3, ZrO2, Ga2O3, Nb2O5, Al2O3, AlOOH and similar components. Solid-state reactions can be used to form the garnet powders. The solid-state reactions involve mixing and calcining precursors. An example of this is Li 6.75 La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 The calcination conditions were 1100°C for 6 hours. After calcination, the powder had more than 90% by weight of the cubic lithium garnet phase. The garnet powder was then dry pressed to form a solid disk with a diameter of about 38 mm and a height of about 20-40 mm. The calcination conditions were 1180°C for 15 hours. After sintering, the sample had a mass of 4.78 g / cm 3 The garnet solid had a density of 3.65×10. The garnet solid was then mechanically cut into thin slices (or films) using a precision diamond blade wet saw. The finished disks were 0.4-0.8 mm thick, with a thickness variation of 0.040 mm across the disk. The films are flat, gas-tight, and strong. The ionic conductivity of this example is 3.65×10. ‐4S / cm. For cell testing, the thin films were cut to 27 mm diameter using a laser. Further dry grinding can be done to obtain thinner disks, such as less than 0.2 mm.

[0082] Example 3 Acid surface treatment of sintered garnet film Prolonged acid treatment resulted in significant H + / Li + Exchange can be effected. The garnet surface, bulk, or both can be "titrated" with a suitable acid to obtain a superprotonated surface or bulk composition. If the degree of exchange is sufficient, the garnet will not behave as a base; that is, when the protonated material is immersed in neutral water, the aqueous pH does not shift significantly to basic. If the garnet is sufficiently neutralized with acid, LiOH will not form upon exposure to ambient atmosphere. Thus, the garnet will not form a lithium carbonate surface layer and can be freely operated in ambient conditions.

[0083] Prior to cell testing, one membrane was kept as a control while another membrane was acid treated according to the method disclosed herein. In the acid treatment, both sides of the thin pellet were immersed in 0.01M HCl (pH 2) acid water solution for 2.5 hours, wiped dry with tissue paper, then rinsed with ethanol and quickly blotted dry with tissue paper in air. The control sample was simply wiped with ethanol saturated tissue paper and air dried. After removing the sample, the soaking solution was tested and the acidity pH2 of the solution was measured.

[0084] FIG. 5 shows TGA traces comparing an untreated garnet control (500) sample with an acid-treated garnet (510) sample after exposure to ambient atmosphere and moisture. The TGA conditions were 2° C. / min to 900° C. for 2 hours and then cooled to RT under air flow. The control sample (500) shows a two-step weight loss, with one step starting below 200° C. and another step above 700° C. The acid-soaked sample shows mainly one step near 500° C. The weight loss of the control sample can be attributed to absorbed water below 200° C. and decomposition of lithium carbonate above 700° C. The weight loss of the acid-soaked sample near 500° C. can be attributed to loss of water from the protonated garnet, leading to phase decomposition. As expected, no carbonate loss was observed for the treated samples. The TGA data demonstrate the importance of avoiding high temperature treatments for proton-exchanged garnets; even conventional drying temperatures can lead to decomposition due to loss of water.

[0085] Based on the weight change due to water loss, the nominal composition of the acid-soaked specimen is Li5H 1.75 La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 It was.

[0086] Example 4 Cell testing of treated and untreated garnet films Cell testing was accomplished as follows: A ceramic-electrolyte protected lithium metal anode cell was assembled in the cell configuration shown in FIG. 2. This configuration is similar to a previously reported scheme, except that there is no microporous polypropylene layer between the lithium metal anode (150) and the LLZO solid electrolyte (see Visco, SJ, et al., Lithium-Air, ELC Encyclopedia of electrochemical power sources, Elsevier, 2009, 4:376-383). In the disclosed cell configuration, the lithium metal was in direct contact with the garnet pellets without any separator layer in between. A mixed solution of LiPF6 in ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC / DMC 1 / 1 (volume ratio), BASF) was used as the anolyte. A mixed solution of 2 M aqueous LiCl and 3 M aqueous NH4Cl was used as the catholyte.

[0087] FIG. 2 is a schematic cross-sectional view of a test cell assembly (200) incorporating a lithium metal anode (150) in contact with a solid garnet electrolyte (110), which is further in contact with an aqueous catholyte (230).

[0088] The test cell assembly (200) can include, for example: a container (202) or similar vessel; a glass tube or cylinder, or similar container (104), positioned over the solid garnet electrolyte (110) and straddling a lithium metal anode (150); The metal rod (206) traverses a seal and holder member (207) disposed at the end of the glass vessel (104), and said metal rod contacts an organic anolyte (260) (such as LiPF6 in ED / DMC; 1:1 (by volume)) within the glass vessel (104); A current collector (208) is attached to the outer end of the metal rod (206); A Ni foil (212) is attached to the inner end of the metal rod (206); The Ni foil (212) is attached to or in electrical contact with the lithium metal anode (150); The cell further comprises a cathode (240), for example supported by the walls of the container (202), and a Ag / AgCl reference electrode (210) in contact with the aqueous catholyte (230).

[0089] FIG. 3 compares the operating cell voltage for acid treated (diamonds, 310) and untreated (squares, 300) garnet pellets (control) as a function of current density. The improved performance of the acid treated garnet samples is evident from the data shown in FIG. 3, which show much lower polarization compared to the untreated samples. The difference in performance is due to the removal of the insulating lithium carbonate surface film in the acid treated samples. At a current density of 0.1 mA / cm for the control garnet cell, 2 When the current density was increased to 0.1 mA / cm, the cell was instantly hyperpolarized within 1 second. In contrast, the cell containing the acid-treated garnet pellet of the present disclosure was hyperpolarized at a current density of 0.1 mA / cm 2 , 0.5mA / cm 2 , and 1.0 mA / cm 2 It worked stably even in

[0090] FIG. 4 shows a 1.0 mA / cm 2 1 shows an exemplary operating cell voltage over an extended period of time for an acid treated garnet pellet at a high current density of 10000 V.

[0091] Although the disclosure has been described with reference to various specific embodiments and techniques, it should be understood that many variations and modifications are possible while remaining within the scope of the disclosure.

[0092] The embodiments of the present invention will be described below in detail.

[0093] EMBODIMENT 1 A bulk composition comprising lithium garnet; and a surface composition comprising a protonated garnet on at least a portion of an outer surface of the lithium garnet, the surface protonated portion of the garnet being compositionally stable in air and insensitive to carbon dioxide. 1. A solid garnet composition comprising:

[0094] EMBODIMENT 2 The above barium garnet is Li7La3Zr2O 12 and The protonated garnet is Li (7‐x) H x La3Zr2O 12 (wherein x is 0.1 to 7).

[0095] EMBODIMENT 3 The lithium garnet is Li 6.75 La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 and The protonated garnet is Li (6.75‐x) H x La 2.9 Ga 0.1 Nb 0.25 Zr 1.75 O 12 (wherein x is 0.1 to 6.75).

[0096] EMBODIMENT 4 4. The composition of any one of embodiments 1-3, wherein the protonated garnet on at least a portion of the outer surface of the lithium garnet includes the entire outer surface of the lithium garnet.

[0097] EMBODIMENT 5 5. The composition of any one of the preceding embodiments, wherein the protonated garnet on at least a portion of the outer surface of the lithium garnet comprises a layer having a thickness of 0.1 to 100 nm.

[0098] EMBODIMENT 6 6. The composition of any one of the preceding embodiments, wherein the surface composition has a lithium concentration of 0.1 to 46 mol %.

[0099] EMBODIMENT 7 7. The composition of any one of embodiments 1-6, wherein the surface composition is substantially free of electrically insulating Li surface species.

[0100] EMBODIMENT 8 8. The composition of any one of the preceding claims, wherein the surface composition comprises a surface that does not include at least one of LiOH, Li2CO3, or a combination thereof.

[0101] EMBODIMENT 9 1. A protective anode structure comprising: A first layer comprising a ceramic electrolyte composition comprising the solid garnet composition of embodiment 1; a second layer comprising a source of lithium metal wherein the first layer and the second layer are in physical contact; and Cathode A composite electrolyte structure comprising:

[0102] EMBODIMENT 10 10. The composite electrolyte structure of embodiment 9, comprising an aqueous catholyte between and in contact with the protected anode structure and the cathode.

[0103] EMBODIMENT 11 11. The composite electrolyte structure of embodiment 9 or 10, wherein the cathode is a lithium cobalt oxide compound.

[0104] EMBODIMENT 12 A method of making the solid garnet composition of embodiment 1, comprising the steps of: The above method: contacting an air-sensitive lithium-containing garnet with a protonic acid to form said solid garnet composition having a protonated garnet surface composition; A method comprising:

[0105] EMBODIMENT 13 13. The method of embodiment 12, wherein the protonic acid is selected from at least one of: an inorganic acid; an organic acid; or a combination of an inorganic acid and an organic acid.

[0106] EMBODIMENT 14 13. The method of embodiment 12, further comprising contacting the air-stable, carbon dioxide insensitive solid garnet composition having the protonated garnet surface with a source of lithium ions to regenerate an air-sensitive lithium-containing solid garnet.

[0107] EMBODIMENT 15 15. The method of embodiment 14, wherein the contacting with the source of lithium ions is accomplished within a sealed cell structure.

[0108] EMBODIMENT 16 15. The method of embodiment 14, wherein the source of lithium ions is lithium metal.

[0109] EMBODIMENT 17 Ion-exchanging the lithium ions on the air-sensitive lithium-containing solid garnet film with protons to form an air-stable, carbon dioxide-insensitive solid garnet electrolyte having a lithium-deficient protonated surface. The passivation method comprising: [Explanation of symbols]

[0110] 100 Schematic diagram 104 Separators, glass tubes or cylinders or similar containers 110 Solid garnet electrolytes, membranes, clean membranes, LLZO, bulk or internal compositions, lithiated surface compositions 115 Exposure 120 LiOH and Li2CO3, surface contamination layer 130HLZO 135 Processing 136 Protonated Surface Compositions 140 Surface-protonated garnet electrolyte products 145 Assembly 150 Lithium metal anode, lithium metal source 155 Tium Ion Flux 160 assembled cells 165 exams 170 Li + Flux 200 Test Cell Assembly 202 Container 206 Metal Rod 207 Holder parts 208 Current collector 210 Ag / AgCl reference electrode 212 Ni foil 230 Aqueous catholyte 240 Cathode 260 Organic Anolyte 500 Garnet control sample not treated with acid 510 Acid-treated garnet sample

Claims

[Claim 1] A membrane of a solid garnet electrolyte, Li 7 La 3 Zr 2 O 12 a bulk composition comprising a first lithium garnet selected from (LLZO) and doped LLZO compositions; and a surface composition comprising a second garnet on at least a portion of an outer surface of the solid garnet electrolyte membrane, the second garnet being a protonated garnet; Including, a second garnet on at least a portion of an outer surface of said solid garnet electrolyte film comprising a layer having a thickness of at least 0.1 mm, and an interior of said solid garnet electrolyte film extending between opposing surfaces of said solid garnet electrolyte film comprising said bulk composition.

Citation Information

Patent Citations

  • Garnet-type ionic conductive oxide and method for manufacturing the same

    JP2012096940A

Cited By

  • Optical fiber characteristic measuring device and optical fiber characteristic measuring method

    CN122730312A

  • Optical fiber characteristic measurement device and optical fiber characteristic measurement method

    EP4807338A1